Recombinant Human Adenovirus-p53 Therapy for the Treatment of Cervical Cancer: A Meta-Analysis - Guo, Yaru; Chen, Jiuzhou; Zhang, Xiwen; Fang, Miao; Xu, Mingna; Zhang, Longzhen; Rao, Enyu; Xin, Yong (Frontiers in Oncology, 2021)
Objectives To evaluate the clinical curative effects and toxicity of recombinant human adenovirus-p53 injection (rAd-p53) plus chemotherapy (CT), radiotherapy (RT), or concurrent chemoradiotherapy (CRT) for the treatment of cervical cancer. Methods We identified 14 eligible studies in the PubMed, Web of Science, Cochrane Library, Embase, CNKI, Wangfangdate, CBM, and VIP databases from their inception to May 2021 and performed meta-analyses using RevMan version 5.3. Results This analysis included 14 studies involving 737 patients. The results of the meta-analysis results showed significantly improved complete remission (odds ratio [OR] = 2.54, 95% confidence interval [CI]: 1.74–3.70, p < 0.00001), partial remission (OR = 1.56, 95% CI: 1.14–2.14, p = 0.006), and object response (OR = 4.47, 95% CI: 3.02–6.60, p < 0.00001) rates in the rAd-p53 combination therapy group compared to those in the CT/RT/CRT group. The results of subgroup analyses of CT/RT/CRT were consistent with the overall results. Regarding the incidence of adverse reactions, only the occurrence rate of fever (OR = 18.21, 95% CI: 10.54–31.47, p < 0.00001) in the rAd-p53 combination group was higher than that in the CT/RT/CRT group. No other significant differences were observed in other adverse reactions. Conclusion RAd-p53 combined with CT/RT/CRT for the treatment of cervical cancer showed significant advantages in efficacy and safety compared to those in the CT/RT/CRT group. Therefore, rAd-p53 has great potential as an effective therapy for cervical cancer. Systematic Review Registration https://inplasy.com/inplasy-2021-5-0058/.